Eco-friendly cellulose-based polymer ligand for toxic metals removal from water sources - Rahman, Md. Lutfor; Yang, Cham Chew; Mohd Sani, Sarjadi; Hazrulrizawati, Abd Hamid; Sarkar, Shaheen M.; Kumar, Sandeep; Kurkuri, Mahaveer D (Elsevier, 2025)
A graft copolymerization process was carried out to anchor an acrylic monomer onto nanocellulose derived from pine wood, resulting in cellulose-graft-poly(methyl acrylate) (cellulose-graft-PMA) via a free radical mechanism. Then, the grafted polymer was treated with hydroxylamine in an alkali medium, resulting in a poly(hydroxamic acid) ligand. The efficiency of this ligand for heavy metal adsorption was systematically investigated. Several parameters, such as pH, initial metal concentration, and adsorption duration, were optimized using batch adsorption experiments, targeting multiple metal ions (Cu2+, Fe2+, Co2+, Ni2+, and Zn2+). The poly(hydroxamic acid) (PHA) exhibited a notable sorption property for Cu2+ ions, achieving the highest capacity of 351 mg/g at pH 6. Other metal ions also showed significant adsorption capacities, with values of 301 mg/g for Fe2+, 261 mg/g for Co2+, 223 mg/g for Ni2+, and 201 mg/g for Zn2+. Trace level of Fe2+ ions can be determined visually using the colorimetric test with PHA. The heavy metals adsorption was pursued using the pseudo first order kinetic model (R2 > 0.994), however, the second order plots showed minimum differences between the qe values and experimental qe values. The adsorption isotherm analysis closely aligned with the Freundlich model, exhibiting a high correlation coefficient (R2 > 0.999). These data indicate that the cellulose-based poly(hydroxamic acid) ligand possesses a heterogeneous surface, which facilitates the creation of multiple layers of adsorption. This adsorbent demonstrates exceptional efficacy in removing toxic metals from industrial wastewater, achieving up to 97 % removal efficiency and presenting a promising approach for controlling wastewater pollution.